Determinants of impulse buying behaviour toward fashion clothing on tiktok live among female students at IIUM - Ramasa Varity (YAYASAN MITRA PERSADA NUSANTARA, 2026)
The growing popularity of social commerce has transformed the way consumers shop, particularly through live-streaming platforms such as TikTok Live. The interactive features of TikTok Live, coupled with promotional and visual marketing strategies, have increased the tendency of consumers to make unplanned purchases. This study investigates the influence of sales promotion, brand equity, and visual appeal on impulse buying behaviour toward fashion clothing on TikTok Live among female students at the International Islamic University Malaysia (IIUM), with perceived risk examined as a mediator. Guided by the Stimulus–Organism–Response (S–O–R) framework, a quantitative survey was conducted among 150 female undergraduate students. Data were analysed using descriptive statistics, zero-order correlation, and partial correlation analyses. The findings revealed that sales promotion, brand equity, visual appeal and perceived risk were positively related to impulse buying behaviour. Among the variables examined, brand equity demonstrated the strongest association with impulse buying behaviour. Furthermore, perceived risk partially mediated the relationships between sales promotion, brand equity, visual appeal, and impulse buying behaviour. These findings suggest that although consumers may perceive certain risks when purchasing fashion clothing through TikTok Live, such concerns do not necessarily prevent impulsive purchasing decisions. The study extends the application of the S–O–R framework in the context of social commerce and contributes to a better understanding of consumer behaviour in live-stream shopping environments. The findings also provide practical insights for marketers, retailers, and content creators in designing effective promotional and communication strategies on TikTok Live.